Коалесценция как асимптотическая стадия процесса внутреннего окисления - Абрамов, Геннадий Серафимович; Абрамов, Михаил Геннадиевич (НТУ "ХПИ", 2019)
Изучена асимптотическая стадия процесса внутреннего окисления – коалесценция в пластинах бинарных сплавов. Показано, что стадии коалесценции Лифшица-Слёзова предшествует достаточно длительная стадия замедленного роста частиц, которая обусловлена потоком легирующего элемента из пластины во внешнюю среду.

The asymptotic stage of the process of internal oxidation – coalescence of binary alloys in the plates is explored. It is shown that the coalescence stage of Lifshitz-Slyozov theory is preceded by a long step of decreasing the particle growth rate, which is caused by the flow of the alloying element from the plate to the external environment.
Coalescence as asymptotic stage of internal oxidation process
Keywords: бинарные сплавы; теория Лифшица-Слёзова; диффузия; пластина; binary alloys; theory of Lifshitz-Slyozov